Level of Appropriation of The Fundamental Competencies of Secondary School Students in Santiago - Rosario-Rodríguez, José Luis (Journal of Neonatal Surgery, 2025)
The full development of fundamental competencies is the main objective pursued by the educational system of the Dominican Republic and for this purpose a specialized curriculum has been designed in which a series of contents, strategies, activities are proposed, as well as particular ways of programming and evaluating competency learning. This study focused on describing the level of appropriation of the fundamental competencies of secondary school students in Santiago. The methodology used was based on a quantitative, descriptive and cross-sectional approach. The study population was made up of 5,000 secondary school students and the sample selected non-probabilistically or by convenience was 535 students. To collect the data, the Fundamental Competencies Questionnaire for the Dominican Republic (CCF-RD) instrument was applied. For data analysis, the statistical software IBM SPSS Statistics version 27 was used. The results show an unfavorable level regarding the Problem Solving Competence, which shows a percentage of 50.2%; Likewise, in Ethical and Citizen Competence 48% and in Communicative Competence 54.6%. It was concluded that the students show weakness in their own mastery of Problem Solving, Ethics and Citizenship competencies, in addition to Communication.